2014
DOI: 10.3139/146.111093
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive modelling of mill loads during hot rolling of AISI 321 austenitic stainless steel

Abstract: A modelled constitutive equation derived from hot working tests to predict hot rolling mill loads is proposed and validated against industrial hot rolling data for AISI 321 stainless steel. Good correlation is found between the predicted mean flow stress, the Zener–Hollomon Z parameter and actual industrial mill load values from mill logs if allowances are made for differences in von Mises plane strain conversion, friction and front or back end tension. The multipass hot working behaviour of this steel was sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Richard et al [11] compared the flow behaviors of 321 and 304 stainless steels, finding that the steady-state stress of 321 was lower than that of 304 for the same Z value. A constitutive model of the rolling load of 321 austenitic stainless steel was subsequently established [12]. Ghazani et al found that the dynamic recovery (DRV) kinetics are more sensitive to deformation rate than deformation temperature [13].…”
Section: Introductionmentioning
confidence: 99%
“…Richard et al [11] compared the flow behaviors of 321 and 304 stainless steels, finding that the steady-state stress of 321 was lower than that of 304 for the same Z value. A constitutive model of the rolling load of 321 austenitic stainless steel was subsequently established [12]. Ghazani et al found that the dynamic recovery (DRV) kinetics are more sensitive to deformation rate than deformation temperature [13].…”
Section: Introductionmentioning
confidence: 99%